AB1047 FLARE PREVENTION IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS TREATED WITH BELIMUMAB VERSUS STANDARD OF CARE: A PROPENSITY SCORE-MATCHED COMPARATIVE, CASE-CONTROL STUDY - Rúa-Figueroa, Í.; Altabás González, I.; Roberts, K.; Casafont-Solé, I.; Hernández, A.; De la Rubia Navarro, M.; Galindo, M.; Salman-Monte, T. C.; Vidal-Montal, P.; Garrote-Corral, S.; Blázquez, M. Á.; Piqueras Garcia, M. M.; et al. (Annals of the rheumatic diseases, 2024)
Background:Belimumab (BLM) is a monoclonal antibody targeting BAFF cytokine, which has shown efficacy and safety in the treatment of systemic lupus erythematosus (SLE). A pooled post-hoc analysis from randomized controlled trials BLISS-52 and BLISS-76 suggested that belimumab is effective reducing the risk of severe flare in patients with SLE [1]. However, data on flare prevention from controlled trials on the subject is lacking.Objectives:We aim to analyse the risk of flare in a multicentre SLE cohort treated with BLM as compared with a control cohort from RELESSER register, under standard of care (SoC).Methods:A longitudinal retrospective study, comparing a multicentre cohort of patients treated with BLM (BLMc) versus a control group of patients treated with standard of care from RELESSER-PROS cohort. We adjusted for a flare risk propensity score (PS) to properly balance covariates (i.e., age, sex, race, disease duration, previous flare, nephritis, serologic activity, baseline SLEDAI, damage index (SLICC/ACR/DI) (SDI) and concomitant treatments: glucocorticoids and antimalarials). Once homogeneous groups were achieved, the distribution of cumulative flares was compared using the Wilcoxon test. The significance level was set at 0.05.Results:Of a total of 1137 SLE Caucasian patients (ACR-97 criteria) (BLMc n = 274; RELESSER n = 853), 102 from BLMc and 134 from RELESSER were PS matched (overall, 236 patients). Differences between BLMc and RELESSER control group, both for covariates and for flares rates are displayed in Table 1. Only the follow-up duration turned out to be greater in BLMc than RELESSER group [4.67 (2.57) vs. 3.11 (0.339) years, respectively, p<0.001)]. Up to 75/134 (56%) patients in RELESSER group underwent ≥ 1 SLE flare during observation period, vs. 32/102 (33.3%) in BLMc. Regarding severe flares, 18/134 (13,4%) in RELESSER vs. 9/102 (8,8%) in BLMc were registered. The mean number of cumulative flares was significatively lower in BLMc (Figure 1); however, not statistically significant differences were found for severe flares comparations.Table 1.Belimumab cohort (BLMc) vs RELESSER control group differencesBLMc(N=102)RELESSER(N=134)P-valueOverall(N=236)Sex female91 (89.2%)123 (91.8%)0.644214 (90.7%)Age at baseline Mean (SD)46.4 (13.2)47.2 (12.3)0.64946.9 (12.7)Disease duration (years) Mean (SD)15.9 (9.86)14.7 (7.94)0.58815.2 (8.82)SLEDAI Mean (SD)4.99 (3.72)4.50 (4.48)0.1184.71 (4.17)C3 or C4 low N (%)50 (49.0%)71 (53.0%)0.046121 (51.3%)Positive anti-DNA N (%)63 (61.8%)76 (56.7%)0.517139 (58.9%)Previous severe flare N (%)23 (22.5%)32 (23.9%)0.93355 (23.3%)Proteinuria (any time) N (%)27 (26.5%)24 (17.9%)0.15551 (21.6%)Hydroxychloroquine N (%)86 (84.3%)115 (85.8%)0.890201 (85.2%)GC dose at baseline ≤5 mg50 (49.0%)46 (34.3%)0.085796 (40.7%) > 5 y < 10 mg13 (12.7%)20 (14.9%)33 (14.0%) ≥10 y <30 mg16 (15.7%)19 (14.2%)35 (14.8%) ≥30 mg1 (0.980%)1 (0.746%)2 (0.847%) Without GC22 (21.6%)48 (35.8%)70 (29.7%)Follow up duration (years) Mean (SD)4.67 (2.57)3.11 (0.339)<0.0013.78 (1.87)Cumulative flare (Global) Mean (SD)0.647 (1.26)1.32 (1.87)<0.0011.03 (1.67) Median [Q1,Q3]0 [0,1.00]1.00 [0,2.00]0 [0,1.25]Severe cumulative flare Mean (SD)0.108 (0.370)0.172 (0.499)0.2760.144 (0.448) Median [Q1,Q3]0 [0,0]0 [0,0]0 [0,0]BLMc: Belimumab cohort; SLEDAI: Systemic lupus erythematosus disease activity index; GC: glucocorticoids (prednisone or equivalent).Figure 1.Conclusion:According to risk factor of SLE-flare adjusted analysis, patients under BLM treatment in real world setting have a decreased risk of flare when comparing with standard of care.Funding:The RELESSER Registry was supported by the Spanish Society of Rheumatology and received financial support from GSK.REFERENCES:[1] van Vollenhoven RF et al, Ann Rheum Dis. 2012;71(8):1343-1349.Acknowledgements:NIL.Disclosure of Interests:Íñigo Rúa-Figueroa GSK, GSK, Irene Altabás González: None declared, Karen Roberts: None declared, Ivette Casafont-Solé: None declared, Andrea Hernández: None declared, Marta De la Rubia Navarro: None declared, Maria Galindo: None declared, Tarek Carlos Salman-Monte: None declared, Paola Vidal-Montal: None declared, Sandra Garrote-Corral: None declared, M. Ángeles Blázquez: None declared, MARIA MERCEDES PIQUERAS GARCIA: None declared, Marina Sánchez Lucas: None declared, Josefina Cortés-Hernández: None declared, Juan Ramón De Dios: None declared, Eva Tomero Muriel: None declared, Paloma Vela Casasempere: None declared, Myriam Gandia Martinez: None declared, Beatriz Frade-Sosa: None declared, Consuelo Ramos Giráldez: None declared, Clara Moriano: None declared, Alejandro Muñoz Jimenez.: None declared, Jaime Calvo Alén: None declared, Raúl Menor-Almagro: None declared, Antonio Fernández Nebro: None declared, José M. Pego-Reigosa: None declared.